Dampak Sertifikasi Halal pada Strategi Pemasaran Produk UMKM di Sektor Makanan - Moh Rihul Azhar; Ahmad Muqorrobin Alamsyah; Natasya Salsa Sabila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Halal certification is a primary requirement for Muslims when choosing food. This requirement is stated in Surah Al-Baqarah, verse 168 of the Quran, which commands Muslims to consume food that is halal and wholesome. Halal certification is assessed not only by the ingredients used but also by the entire production process, from processing and raw material use, transportation, to sales and consumption methods. In Indonesia, the development of halal products continues to grow rapidly in line with the large Muslim population. However, public understanding of halal certification, particularly for food and beverage products, remains relatively low. Based on this situation, this study examines the impact of halal certification on the marketing strategies of MSMEs in the food sector. This research seeks to answer two main questions: first, to what extent do MSMEs understand the importance of halal certification? and second, does the existence of halal certification influence consumer purchasing interest? The study used a library method, reviewing a variety of relevant literature, and an empirical approach to obtain data directly from the public.